Urbanization and genetic homogenization in the medieval Low Countries revealed through a ten-century paleogenomic study of the city of Sint-Truiden - Beneker, Owyn; Molinaro, Ludovica; Guellil, Meriam; Sasso, Stefania; Kabral, Helja; Bonucci, Biancamaria; Gaens, Noah; D'Atanasio, Eugenia; Mezzavilla, Massimo; Delbrassine, Hélios; Braet, Linde; Lambert, Bart; et al. (Genome biology, 2025)
BACKGROUND: Processes shaping the formation of the present-day population structure in highly urbanized Northern Europe are still poorly understood. Gaps remain in our understanding of when and how currently observable regional differences emerged and what impact city growth, migration, and disease pandemics during and after the Middle Ages had on these processes. RESULTS: We perform low-coverage sequencing of the genomes of 338 individuals spanning the eighth to the eighteenth centuries in the city of Sint-Truiden in Flanders, in the northern part of Belgium. The early/high medieval Sint-Truiden population was more heterogeneous, having received migrants from Scotland or Ireland, and displayed less genetic relatedness than observed today between individuals in present-day Flanders. We find differences in gene variants associated with high vitamin D blood levels between individuals with Gaulish or Germanic ancestry. Although we find evidence of a Yersinia pestis infection in 5 of the 58 late medieval burials, we were unable to detect a major population-scale impact of the second plague pandemic on genetic diversity or on the elevated differentiation of immunity genes. CONCLUSIONS: This study reveals that the genetic homogenization process in a medieval city population in the Low Countries was protracted for centuries. Over time, the Sint-Truiden population became more similar to the current population of the surrounding Limburg province, likely as a result of reduced long-distance migration after the high medieval period, and the continuous process of local admixture of Germanic and Gaulish ancestries which formed the genetic cline observable today in the Low Countries.
Keywords: Palaeo-genomics; Humans; Urbanization; Belgium; mor; populační genetika; Flanders; History, Medieval; Genetics, Population; Medieval; genomika; Migration; lidé; genetická variace; Genetic Variation; Belgie; Plague; urbanizace; genom lidský; Low countries; Genomics; Genome, Human; dějiny středověku